CYBER WARFARE AND INTERNATIONAL CYBER LAW: WHITHER? - Miodrag N. Simović; Živorad Rašević; Vladimir M. Simović (Revija za kriminologiju i krivično pravo)
This paper analyses historical, sociological and normative aspects of the cyber violence in international relations and international law, aiming to assess the adequacy of the extant international norms for its regulation. It results with the knowledge on the lack of international cooperation and a universal approach, the instrumentalisation of the internet as a means of warfare, lacunae in the relevant legal framework, and the peril of compromisation of the international law. Since the social jeopardy of activities in the cyberspace is hardly measurable and subjected to highly arbitrary interpretations, the problem of the uncertain peacetime or belligerent legal qualification of cyber activities is exposed. The other serios problem is a high risk from potentially disproportional responses of states to the cyber violence. Especially due to the lack of universal international institutions in the field of cyber, it must be concluded that the international lege lata applicable to the cyber violence is not adequate and sustainable. The progressive development of international cyber law is thus suggested, through the pacification of the internet and the international criminalisation of cyber violence.